The effect of red blood cell aggregation on velocity and cell-depleted layer characteristics of blood in a bifurcating microchannel - Sherwood, J.M.; Dusting, J.; Kaliviotis, Efstathios; Balabani, Stavroula (My University, 2012)
Red blood cell (RBC) aggregation is a multifaceted phenomenon, and whether it is generally beneficial or deleterious remains unclear. In order to better understand its effect on microvascular blood flow, the phenomenon must be studied in complex geometries, as it is strongly dependent on time, flow, and geometry. The cell-depleted layer (CDL) which forms at the walls of microvessels has been observed to be enhanced by aggregation; however, details of the characteristics of the CDL in complex regions, such as bifurcations, require further investigation. In the present study, a microchannel with a T-junction was used to analyze the influence of aggregation on the flow field and the CDL. Micro-PIV using RBCs as tracers provided high resolution cell velocity data. CDL characteristics were measured from the same data using a newly developed technique based on motion detection. Skewed and sharpened velocity profiles in the daughter branches were observed, contrary to the behavior of a continuous Newtonian fluid. RBC aggregation was observed to increase the skewness, but decrease the sharpening, of the velocity profiles in the daughter branches. The CDL width was found to be significantly greater, with a wider distribution, in the presence of aggregation and the mean width increased proportionally with the reciprocal of the fraction of flow entering the daughter branch. Aggregation also significantly increased the roughness of the interface between the CDL and the RBC core. The present results provide further insight into how RBC aggregation may affect the flow in complex geometries, which is of importance in both understanding its functions invivo, and utilizing it as a tool in microfluidic devices.
Keywords: Bifurcation (mathematics); Blood; Blood vessels; Cytology; Geometry; Intersections; Microchannels; Newtonian liquids; Velocity